Drunk and doubly deviant?: the role of gender and intoxication in sentencing assault offences - Lightowlers, Carly (The British journal of criminology, 2019)
Little is known about how alcohol intoxication impacts sentence outcomes. This study assesses whether intoxication differentially aggravates sentence outcomes for male and female defendants of assault offences. It does so by modelling the probability of custody and sentence severity using the Crown Court Sentencing Survey, including interaction terms to account for the gendered application of intoxication as a sentencing factor. The main finding is that the aggravation afforded to female defendants is twice than that afforded to males where intoxication in present and when controlling for relevant case characteristics. The study spotlights how cases of assault are processed through the criminal justice system and raises concerns with how gender equality is interpreted in sentencing practice with reference to alcohol intoxication.